Ultra-Luminous Infrared Mergers: Elliptical Galaxies in Formation? - Genzel, R; Tacconi, L; Rigopoulou, D; Lutz, D; Tecza, M (Institute of Physics Publishing, 2001)
We report high quality near-infrared spectroscopy of 12 ultra-luminous infrared galaxy mergers (ULIRGs). Our new VLT and Keck data provide ~0.5" resolution, stellar and gas kinematics of these galaxies most of which are compact systems in the last merger stages. We confirm that ULIRG mergers are 'ellipticals-in-formation'. Random motions dominate their stellar dynamics, but significant rotation is common. Gas and stellar dynamics are decoupled in most systems. ULIRGs fall on or near the fundamental plane of hot stellar systems, and especially on its less evolution sensitive, r(eff)-sigma projection. The ULIRG velocity dispersion distribution, their location in the fundamental plane and their distribution of v(rot)*sin(i)/sigma closely resemble those of intermediate mass (~L*), elliptical galaxies with moderate rotation. As a group ULIRGs do not resemble giant ellipticals with large cores and little rotation. Our results are in good agreement with other recent studies indicating that disky ellipticals with compact cores or cusps can form through dissipative mergers of gas rich, disk galaxies while giant ellipticals with large cores have a different formation history.